Nanostructured TiO2-based composites for light absorption - Santos, Dayse Iara dos [UNESP]; Modesto Junior, Olayr [UNESP]; Scalvi, Luis Vicente de Andrade [UNESP]; Tabata, Américo Sheitiro [UNESP] (Trans Tech Publications Ltd, 2014)
Metal oxidenanocomposites were prepared by two different routes: polyol and sol-gel. Characterization by X ray diffraction showed that the first processproducesdirectly a two-phase material, while the sol-gelpowder never showed second phase below 600 degrees C. Light spectroscopy of the treated powders indicated similarities for the processed materials. Although the overall material compositions are about the same, different structural characteristics are found for each processing. With the exception of Ti-Zn materials, all the double metal oxide powders showed higher absorbance than either TiO2 powder.
Keywords: Semiconductor nanocomposites; Polyol method; Ti-xerogel; TiO2-ZnO composite; TiO2-CuO composite; TiO2-ZrO2 composite; Light absorption in nanocomposites